ANALISIS FRAMING PEMBERITAAN KASUS ‘BJORKA’ DI CNN INDONESIA PADA 12 SEPTEMBER - Gunther, Evangelin Baliata; Gelgel, Ni Made Ras Amanda; Purnawan, Ni Luh Ramaswati; Cahyani, Dewi Yuri (E-Jurnal Medium, 2024)
Cases of data breaches have occurred several times in Indonesia. One of the cases that is in the public spotlight is the data leak case carried out by a figure named “Bjorka”. This anonymous figure has carried out a series of data breaches involving public data and the personal data of state officials. The issue of data leakage then grew, and both print and online media outlets covered it extensively. This study tries to ascertain how the "Bjorka" case was covered by CNN Indonesia on September 12, 2022. In this study, the framing analysis technique developed by Robert N. Entman is used in a qualitative descriptive approach. On September 12, 2022, CNN Indonesia's online news service served as the research's data source. According to the study's findings, CNN Indonesia separated the three main concerns it used to shape the public's perceptions of the Bjorka case into three categories.